Democratic Evaluation (Better Evaluation)
Democratic Evaluation is an approach where the aim of the evaluation is to serve the whole community. This allows people to be informed of what others are doing and sees the evaluator as someone who brokers the process. It generally focuses on inclusive practices which foster participation and collaboration. However it is also used as a means of ensuring public accountability and transparency.